2019
DOI: 10.2147/ott.s217916
|View full text |Cite
|
Sign up to set email alerts
|

<p>NCAPG Promotes The Proliferation Of Hepatocellular Carcinoma Through PI3K/AKT Signaling</p>

Abstract: PurposeStudies show that high expression of non-SMC condensin I complex subunit G (NCAPG) is associated with many tumors. In this study, we explore the mechanism by which NCAPG promotes proliferation in hepatocellular carcinoma (HCC).Patients and methodsLiver cancer and paracancerous tissue specimens of 90 HCC patients were collected, and expression levels of NCAPG in these tissues and cell lines were evaluated by Western blotting and immunohistochemistry. HCC cells were transfected with siRNAs and plasmids, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
89
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(99 citation statements)
references
References 47 publications
10
89
0
Order By: Relevance
“…Significantly, AKR1B10 was not included in the GSE84005 dataset or NCAPG and LAPTM4B in the GSE45114 dataset. However, close association of these three genes with the progression of HCC has been recently reported ( DiStefano and Davis, 2019 ; Gong et al, 2019 ; Wang F. et al, 2019 ). The RRA method effectively maximizes the retention of hub genes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Significantly, AKR1B10 was not included in the GSE84005 dataset or NCAPG and LAPTM4B in the GSE45114 dataset. However, close association of these three genes with the progression of HCC has been recently reported ( DiStefano and Davis, 2019 ; Gong et al, 2019 ; Wang F. et al, 2019 ). The RRA method effectively maximizes the retention of hub genes.…”
Section: Resultsmentioning
confidence: 95%
“…For example, as shown in Figure 1B , AKR1B10, NCAPG, and LAPTM4B exist in multiple datasets and would therefore be lost if the datasets were simply merged. However, these genes are closely related to the progression of HCC ( DiStefano and Davis, 2019 ; Gong et al, 2019 ; Wang F. et al, 2019 ). Furthermore, in dataset GSE39791, logFC values of some of the top 20 DEGs were less than 1.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously found that NCAPG promotes proliferation, metastasis, and recurrence in HCC 12 . RNA sequencing revealed that overexpression of NCAPG can induce cell proliferation and inhibit apoptosis via activation of the PI3K-AKT signaling pathway in HCC 17 . Upregulated NCAPG also correlated positively with the cell proliferation and poor survival in BC as well as the poor disease-free survival and advanced clinical stage in castration-resistant prostate cancer 14 , 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Upregulation of NCAPG has been suggested to facilitate cell proliferation in gastric cancer 15 . Moreover, ectopic NCAPG was shown to promote cell proliferation, metastasis, differentiation in HCC and was associated with poor TNM stages, poor survival, and tumor recurrence in HCC patients 16,17 . Although NCAPG has previously been reported to be overexpressed and correlated with poor survival in BC 18,19 , its biological role and mechanism have not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of enhancing the proliferation of HCC, NCAPG shares similar mechanisms with TTK. NCAPG, which is also called non-SMC condensin I complex subunit G, and the overexpression of NCAPG leads to an enhanced proliferation and reduced apoptosis of HCC through PI3K/AKT signaling pathway (52) Ying et al .in 2018 (54) reported that ZWINT promotes the proliferation of HCC through the regulation of cell-cycle-related proteins such as CDK1, PCNA, etc. The regulation is also mentioned in the top ten hub gene network, which is corresponding to our ndings.…”
Section: Discussionmentioning
confidence: 99%